Review: Failure of current digoxin monitoring for toxicity: new monitoring recommendations to maintain therapeutic levels for efficacy - Gona, Sridhar Rao; Rosenberg, Joel; Fyffe-Freil, Ria C.; Kozakiewicz, Janet M.; Money, Mary E. (Frontiers in Cardiovascular Medicine, 2023)
The current recommendations for monitoring digoxin, a narrow therapeutic index drug, are limited to confirming medication use or investigating suspicion of toxicity and fail our oath to do no harm. Numerous meta-analyses evaluating digoxin use consistently recommend frequent monitoring to maintain the level of 0.5 to ≤1.0 ng/ml because higher levels lead to increased morbidity and mortality without benefit. Data from the United States National Poison Control Center (2012–2020) show annual deaths due to digoxin of 18–36 compared to lithium's 1–7, and warfarin's 0–2 respectively. The latter drugs also have narrow therapeutic indexes like digoxin yet are more carefully monitored. Recognition of digoxin toxicity is impaired as levels are not being routinely checked after medications are added to a patient's regimen. In addition, providers may be using ranges to guide treatment that are no longer appropriate. It is imperative that monitoring guidelines and laboratory therapeutic levels are revised to reduce morbidity and mortality due to digoxin. In this review, we provide a comprehensive literature review of digoxin monitoring guidelines, digoxin toxicity, and evidence to support revising the ranges for serum digoxin monitoring.